Gender-Biased Language of the Workplace - O. O. Stroi (Дискурс, 2020)
Introduction. The World Economic Forum reports that in 2018 only 34 % of managerial positions globally were occupied by women, and the wage gap between male and female employees constitutes 63 % on average with only 67 % of women doing paid jobs. While there are multiple economic, social and cultural reasons why women are not being employed or promoted, the goal of the present study is to look at the linguistic biases hindering women's careers. We will be looking at the previous research devoted language of job advertisements, resumes, job interviews, letters of recommendation and performance reviews in order to uncover the gender-specific language and its possible effect on women's employability and analyzing the language of the public professional recommendations.Methodology and sources. We looked at the research devoted to the gender-biased language in the workplace in the last ten years which helped us to formulate three hypotheses. Then we tested these hypotheses against the data we collected from 80 public professional profiles of male and female managers. Our goal was to discover quantitative differences in usage of communal and agentic terms in reference to men and women.Results and discussion. Confirming previous findings we found out that the difference in usage of agentic terms is statistically significant across genders. Men are more often described as "leaders", "mentors", and "achievers" and attributed sense of humor than women. On the other hand, communal terms are equally used for both male and female managers.Conclusion. The gendered language can be found in all texts related to recruitment and promotion and maybe one of the reasons for the professional gender-gap. Continuous research on the topic and bringing awareness to human resource professionals and career coaches may be helpful in improving inclusion and diversity especially in higher management of the companies and in academia.